(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article discusses promising wild species of essential oil plants growing in the mountainous areas of Kyrgyzstan. The place of growth, the content of essential oils and its use in official and folk medicine are given. This information may be useful to those interested in collecting medicinal plants. Hundreds of species of medicinal and essential oil plants are considered promising, of which not all species have been studied, and the species mentioned in the article found in the natural conditions of the republic have already been included in the State Pharmacopoeia. Based on the analysis of literary sources and data from the laboratory of medicinal and essential oil plants of the Institute, the content of essential oil was identified and the place where this species grows was given. The studies carried out on the presence of wild essential oil plants in the flora of Kyrgyzstan are not final and, of course, require additional clarification and in-depth comprehensive study of each species.